Handbook of paper and paperboard packaging technology - Kirwan, Mark J. (Chichester, West Sussex ; Ames, Iowa : Wiley-Blackwell, 2013)
The definitive industry reference on the paper and paperboard packaging sector. Now in a fully revised and updated second edition, this book discusses all the main types of packaging based on paper and paperboard. It considers the raw materials, the manufacture of paper and paperboard, and the basic properties and features on which packaging made from these materials depends for its appearance and performance. The manufacture of twelve types of paper- and paperboard-based packaging is described, together with their end-use applications and the packaging machinery involved. The importa.
2.7.8 Emissions associated with product use2.7.9 Emissions associated with product end of life; 2.7.10 Avoided emissions and offsets; 2.8 Conclusion; References; 3 Paper-based flexible packaging; 3.1 Introduction; 3.2 Packaging needs which are met by paper-based flexible packaging; 3.2.1 Printing; 3.2.2 Provision of a sealing system; 3.2.3 Provision of barrier properties; 3.3 Manufacture of paper-based flexible packaging; 3.3.1 Printing and varnishing; 3.3.2 Coating; 3.3.3 Lamination; 3.4 Medical packaging; 3.4.1 Introduction to paper-based medical flexible packaging; 3.4.2 Sealing systems.
Earlier edition has title: Paper and paperboard packaging technology.
Includes bibliographical references and index.
Print version record.
Keywords: Paper containers; Paperboard; Packaging; Packaging; Paper containers; Paperboard; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Packaging; Paper containers; Paperboard; Electronic books